Implementation of the Discrete Wavelet Transform Used in the Calibration of the Enzymatic Biosensors - Alonso, Gustavo A.; Gutiérrez, Juan Manuel; Marty, Jean-Louis; Muñoz, Roberto (IntechOpen, 2011)
None